Xerostomia: An overview - Jitender Reddy Kubbi; Loka Ravali Reddy; Lakshmi Srujana Duggi; Harisha Aitha (Journal of Indian Academy of Oral Medicine and Radiology, 2015)
Xerostomia is a subjective sensation of dry mouth with objective evidence of decreased salivary flow. It is a multifactorial condition which increases the risk of oral diseases and has a significant effect on the person′s quality of life. So, these patients need special care for maintenance of oral and general health. We, being oral health care professionals, it is our responsibility to diagnose and treat the condition accordingly using a multidisciplinary approach. This paper enlightens the etiology and management of xerostomia.